Attrition issues among technical female graduates in Malaysian construction industry / Nur Amani Yazid and Noor Aisyah Asyikin Mahat - Yazid, Nur Amani; Mahat, Noor Aisyah Asyikin (2018)
Women in the construction industry struggle mostly with sexist attitudes, behaviours and perceptions in the workplace. The main concern is the inflexible working practices which often lead to problems regarding their work-life balance. Previous research indicated that women continue to take responsibility for household tasks and child-upbringing despite spending many hours working outside the house. Their job satisfaction decreases while their stress increases when there is a conflict between work and family roles. This will later turn the female workers to leave and quit the jobs. This research represents the finding of the attrition issues among technical female graduates in construction industry. The objective of the research is to provide a comprehensive review on the technical female graduates' leaving the construction industry and to analyse the factors contribute to attrition issues towards construction industry development. This research adopted quantitative approach of research methodology. Fifty (50) sets of questionnaires were distributed among female graduates who have technical backgrounds in either construction management, architecture, quantity surveying and civil engineering. Research finding shows that the main factors contribute to attrition issues are working environment, work family-lifestyle balance, high levels of stress, and better opportunity for promotion and career development.